ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PELUNASAN PIUTANG DOORING PADA PT YUDHISTIRA PERKASA ABADI - Istiqomah, Baibatul; Safira, Selma Putri (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the internal control system over accounts receivable settlement at PT Yudhistira Perkasa Abadi, particularly in its dooring services. The focus of the study lies in how the company implements internal control principles,such as segregation of duties, transaction authorization, document completeness, and internal monitoring to support the accuracy and timeliness of receivables settlement. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation review. The results indicate that the elements of internal control based on the COSO framework have been generally implemented, including control environment, risk assessment, control activities, information and communication, and monitoring. However, weaknesses were found in the monitoring aspect, especially the absence of an independent audit unit and the suboptimal execution of cross-verification. Therefore, it is recommended that the company strengthen internal supervision and its authorization structure to enhance the effectiveness of receivables management and maintain cash flow stability.